Childhood in Kinship Care A Longitudinal Investigation - Skoglund, Jeanette (Taylor & Francis, 2022)
Kinship foster care involves placing children who cannot live at home in foster care with other members of their family or close network. This book sheds light on different aspects of kinship care development and practice. Using a 20-year longitudinal research study from Norway, this book shows the historical development of kinship care in Norway, research on kinship care, and how family life and relations are negotiated and lived in the span between private and public sphere. It includes the perspectives of the children, their parents and their relatives who have functioned as foster parents. Recognising that kinship care is complex, and needs to be understood and studied from different perspectives, the book describes, analyses and discusses a number of subjects: kinship care in a child welfare historical context, families who are part of kinship care and their perspectives, the formal frameworks around kinship care, and research approaches which have dominated research into kinship care. This book will be of interest to all scholars, students and professionals working in social work and child welfare more broadly, both in the Nordic countries and in a wider international context.